Concurrent Intracranial and Lumbar Chronic Subdural Hematoma Presenting with Severe Lumbar Radiculopathy: A Case Report - Thapa, Dinesh Kumar; Jha, Keshav; Bhagat, Manisha Kumari (Eastern Green Neurosurgery, 2026)
Background: Concurrent intracranial and spinal chronic subdural hematomas are rare and may be difficult to diagnose. Intracranial CSDH usually presents with headache or neurological deficits, whereas spinal SDH may cause back pain and radiculopathy.Case Presentation: A 57-year-old man presented with 10 days of severe low back pain radiating to both lower limbs, associated with weakness and abnormal gait. Lumbar MRI showed a subdural hematoma extending from T12/L1 to S1/S2 with cauda equina crowding. Brain MRI revealed bilateral chronic intracranial subdural hematomas without significant mass effect or midline shift. The patient was managed conservatively, and his symptoms resolved completely within 2 weeks.Conclusion: Severe lumbar radiculopathy may be the initial presentation of concurrent intracranial and spinal CSDH. Brain and spine imaging should be considered in older patients with unexplained spinal symptoms, especially after minor trauma or anticoagulant use.